Indian Democracy And Importance Of Uniform Civil Law With Special Reference To Women Empowerment In India (International Journal of Food and Nutritional Sciences, 2022)
Indian Democracy is made by the People of India so its very crucial to understand the concerned conception of Uniform Civil law Code. Present article is focused on Indian Democracy and Important of Uniform Civil Law. If we see at the preamble of the Constitution there is a term secular and the citizens are guaranteed their freedom of religion and being a secular State, it should not interfere in matter of individuals’ religion. Indian secularism imposes a negative command on the State to not to identify with any specific religion and treat its citizen with the spirit of “Sarva Dharm Sambhava” It has been argued by few scholars that the Indian society is not socially developed enough to utilize the “Uniform civil code” [Herein after UCC and thus UCC is still is a topic of discussion in Indian context]. The reason behind it, as the researcher has observed, is that India is a vast Country with diverse cultures, religion, etc. Enforcement of UCC can be seen as unnecessary imposition of State law, which would infringe many religious practices and cultures.Women's empowerment is defined as the process of improving the economic, social, and political position of traditionally underprivileged women in society. The research is entirely based on secondary sources. Despite the government's efforts, women in India are generally disempowered and have a lower status than men, according to the report. It has been discovered that women continue to accept unfair gender standards in society. The study continues by stating that women's empowerment is facilitated by access to health, education, employment, and changes in social and political systems.